KEDUDUKAN PANCASILA DALAM POLITIK HUKUM INDONESIA MENUJU NEGARA HUKUM KESEJAHTERAAN (WELFARE STAAT) - Sujasmin, Sujasmin (Sekolah Tinggi Hukum Bandung, 2012)
In the development of law in Indonesia, it has already changed in the fields of law, economy, culture, religion, and also technology. Therefore, politic of law in the law reform in Indonesia which puts priority on the making of law materials should adapt and accommodate the needs of society, and the implementation of the provision of law and the clearness of institutional function should be performed firmly as well as the establishment of law upholders, and finally it can create a welfare staat. Indonesia has an ideal principle, Pancasila as it is contained in the 1945 Constitution. Pancasila in the system of Indonesian politic of law has a philosophy of life, and becomes a basis of the State of the Republic of Indonesia or basis of Indonesian philosophy which has a vast philosophy study in Indonesian politic of law, both from the historical aspect and the making of law which should reflect highest values contained in Pancasila, and it should not be separated from politic of law policy.Keywords: politic of law; law upholder; State of law